2017
DOI: 10.3389/fphys.2017.00196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sesame (Sesamum indicum L.) Supplementation on Creatine Kinase, Lactate Dehydrogenase, Oxidative Stress Markers, and Aerobic Capacity in Semi-Professional Soccer Players

Abstract: Nutritional intervention with antioxidants rich foods has been considered a strategy to minimize the effects of overtraining in athletes. This experimental, randomized, and placebo-controlled study evaluated the effects of consumption of sesame (Sesamum indicum L.) on muscle damage markers, oxidative stress, systemic inflammation, and aerobic performance in male semi-professional soccer players. Twenty athletes were randomly assigned to groups that received 40 g (two tablespoons) per day of sesame or a placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This review outlined a wide assortment of ingredients, functional foods, and dietary supplements that have been shown to affect EIMD-related outcomes, with varying levels of success. In addition to the topics covered in the present review, many emergent nutritional and supplementation strategies have not been fully explored, including black tea-sourced polyphenols [161], blueberries [162], chondroitin sulfate [163], high chlorogenic acid coffee [164], fasting [165], garlic [166], leucine metabolites such as HICA [167], lemon verbena [168], lychee [169], mate tea [170], pequi fruit [171, 172], quercetin [173], saffron [174], selenium [175], sesame [176], spinach [177], and tomato juice [178, 179]. Future research in these nascent areas may shed new light on potential treatment options for EIMD.…”
Section: Discussionmentioning
confidence: 99%
“…This review outlined a wide assortment of ingredients, functional foods, and dietary supplements that have been shown to affect EIMD-related outcomes, with varying levels of success. In addition to the topics covered in the present review, many emergent nutritional and supplementation strategies have not been fully explored, including black tea-sourced polyphenols [161], blueberries [162], chondroitin sulfate [163], high chlorogenic acid coffee [164], fasting [165], garlic [166], leucine metabolites such as HICA [167], lemon verbena [168], lychee [169], mate tea [170], pequi fruit [171, 172], quercetin [173], saffron [174], selenium [175], sesame [176], spinach [177], and tomato juice [178, 179]. Future research in these nascent areas may shed new light on potential treatment options for EIMD.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Additionally, elevated serum LDH levels are an independent risk factor for poor prognosis in several cancers including HCC, gastric carcinoma, lung cancer, colorectal cancer, nasopharyngeal carcinoma, and breast cancer. 20 24 Elevated serum LDH levels have been shown to be involved in cancer pathogenesis via inflammation; 25 27 conversely, lactate dehydrogenase inhibitors can reverse inflammation-induced changes in cancer cells. 28 , 29 Increased LDH levels alone are therefore a poor prognostic factor in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to indicate that cycling (a predominantly concentric contraction sport) is not considered to be a damaging per se. Similarly, da Silva et al (2017) found no effect of supplementation with 6 g of citrulline malate on muscle soreness or serum CK during the 72 h recovery period after a leg press and hack squat exercise when compared to placebo control. Finally, a more recent study (Chappell et al, 2018) reported that acute citrulline malate supplementation (4.21 g citrulline and 3.79 g malate) actually increased total muscle soreness during the 72-h period after isokinetic knee extensions (10 sets of 10 repetitions, 70% MVC) compared to placebo (6 g of citric acid) in 5 females and 13 males resistance-trained.…”
Section: Interventions With a Modest Evidence Base L-citrulline And Watermelon Juicementioning
confidence: 94%
“…In contrast to these promising results with watermelon juice enriched with L-citrulline other studies have reported no benefit (Shanely et al 2016;da Silva et al 2017;Chappell et al 2018). For example, Shanely et al (2016) reported no effect of watermelon puree consumption (980 mL/day for 14 days) on markers of inflammation in trained cyclists after a 75 km time trial.…”
Section: Interventions With a Modest Evidence Base L-citrulline And Watermelon Juicementioning
confidence: 97%